2004
DOI: 10.1001/archinte.164.10.1098
|View full text |Cite
|
Sign up to set email alerts
|

Disability and Chronic Fatigue Syndrome

Abstract: For questions of disability and employment in CFS, the limitations inherent in the current literature are extensive. Methodologically rigorous, longitudinal, and interventional studies are needed to determine baseline characteristics that are associated with the inability to work and interventions that are effective in restoring the ability to work in the CFS population. Simple and consistent evaluations of functional capacity in patients with CFS are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 78 publications
7
38
0
4
Order By: Relevance
“…Recent studies of CFS (e.g., Friedberg & Sohl, 2009b;Jason et al, 2007) suggest a wide range of functioning. Because rates of employment and disability vary considerably in studies of CFS and FM (Reisine, Fifield, Walsh, & Feinn, 2003;Ross et al, 2004), generalizations may convey inaccurate impressions of functional status.…”
Section: Measuring Physical Functioningmentioning
confidence: 99%
“…Recent studies of CFS (e.g., Friedberg & Sohl, 2009b;Jason et al, 2007) suggest a wide range of functioning. Because rates of employment and disability vary considerably in studies of CFS and FM (Reisine, Fifield, Walsh, & Feinn, 2003;Ross et al, 2004), generalizations may convey inaccurate impressions of functional status.…”
Section: Measuring Physical Functioningmentioning
confidence: 99%
“…Neurocognitive dysfunction in patients with CFS manifests primarily in the form of concentration/attention problems, memory impairment, poor word-finding ability, decreased information-processing speed, motor slowing, and mental exhaustion (Busichio et al, 2004;Deluca et al, 2004;Michiels and Cluydts, 2001). Cognitive dysfunction in CFS patients has been found in some, but not all, objective studies (Afari and Buchwald, 2003;Michiels and Cluydts, 2001;Ross et al, 2004;Wearden and Appleby, 1997). This heterogeneity may stem from the relative presence of mental fatigue in the patients with CFS.…”
Section: Introductionmentioning
confidence: 99%
“…Several prognostic studies have examined predictors of fatigue and found illness attributions and psychological problems to be important and consistent predictors of outcome in fatigue (Chalder et al 2003 ;Schmaling et al 2003;Skapinakis et al 2003 ;Huibers et al 2004b). Despite a considerable number of these prognostic studies, few data are available on occupational outcomes in studies of chronic fatigue and chronic fatigue syndrome (CFS) (Ross et al 2004 ;Cairns & Hotopf, 2005). Knowledge of prognostic factors related to occupational outcomes is important because persistent fatigue is strongly associated with functional status and can lead to absenteeism and even full work incapacity (Van Amelsvoort et al 2002 ;Janssen et al 2003 ;Ross et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a considerable number of these prognostic studies, few data are available on occupational outcomes in studies of chronic fatigue and chronic fatigue syndrome (CFS) (Ross et al 2004 ;Cairns & Hotopf, 2005). Knowledge of prognostic factors related to occupational outcomes is important because persistent fatigue is strongly associated with functional status and can lead to absenteeism and even full work incapacity (Van Amelsvoort et al 2002 ;Janssen et al 2003 ;Ross et al 2004). These associations between fatigue, functional status and work status could grow stronger and become intertwined in the course of time, as a result of which the prognosis of fatigue could take a turn for the worse.…”
Section: Introductionmentioning
confidence: 99%